Kajian Kualitas Nata de Nira Siwalan (Borassus flabelliver L.) dengan Variasi Macam Gula dalam Beberapa Konsentrasi sebagai Materi Handout Biologi Kelas XII MAN Pamekasan - Chandra Kirana; Utami Sri Hastuti; Endang Suarsini (Universitas Sebelas Maret, 2016)
The purpose of this study include: (1) analyze the quality of nata de sap of palm with a wide variety and concentration of sugar in terms of weight and fiber content nata; (2) develop a handout materials for students of class XII Biotechnology MAN Pamekasan based on research results; and (3) analyze the quality of handouts developed as the implementation of research results. The research method there are two stages of experiment and development. Research conducted at the Laboratory of Microbiology Faculty UM Malang in January-March 2013. The results showed that: (1) there is a wide influence on the quality of sugar palm sap nata de nata either by weight or fiber content; (2) No effect of sugar concentration on the quality of nata de sap siwalan both based on the weight of nata and fiber content; (3) handout Biotechnology has been eligible for use in helping Biology teaching and learning activities in MAN Pamekasan with excellent qualifications based on an assessment by experts validator Microbiology and excellent materials based on an assessment by experts validator teaching materials.Keywords: nata de nira siwalan, quality, research based handout